A separator and a battery
By using a ceramic layer with a porous structure in the lithium-ion secondary battery separator, combining inorganic particles and the first polymer, the problem of insufficient needle-punching strength when the existing separator improves porosity and fast charging performance is solved, and the high long cycle performance and safety performance of the battery are achieved.
Patent Information
- Application Number
- CN202411607370.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
While the existing lithium-ion secondary battery separators improve porosity and fast charging performance, it is difficult to maintain needle puncture strength, affecting the self-discharge and safety performance of the battery.
A separator including a substrate and a ceramic layer is used, which consists of inorganic particles and a first polymer, has a porous structure, and controls the number and average diameter of pores with a diameter of ≥0.5 μm to ensure the porosity and thermal stability of the ceramic layer.
It achieves the improvement of the battery's long cycle performance and safety performance while maintaining high porosity and fast charging performance, and reduces the cost of the diaphragm.
Smart Images

Figure CN119153896B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a diaphragm and a battery comprising the diaphragm. Background Art
[0002] With the popularization of 3C products and the rise of the electric vehicle market, the demand for lithium-ion secondary batteries is increasing. As a key component of lithium-ion secondary batteries, the separator directly affects the safety, long cycle, fast charging and other performance of lithium-ion secondary batteries.
[0003] In order to improve the long cycle performance and fast charging performance of lithium-ion secondary batteries, the traditional solution is mainly to increase the porosity of the substrate or coat a layer of glue on the surface of the diaphragm. Among them, increasing the porosity of the substrate can improve the ion conductivity of the diaphragm, thereby improving the fast charging ability of the battery, but with the increase of the porosity of the substrate, the puncture strength performance of the diaphragm will decrease, thereby affecting the self-discharge, safety and other performances of the battery; coating a layer of glue on the surface of the diaphragm can improve the interface stability between the diaphragm and the positive active layer and the negative active layer, thereby improving the long cycle ability of the battery, but coating an extra layer of glue will increase the cost of the diaphragm, and coating a layer of glue will reduce the fast charging performance of the battery to a certain extent. Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a diaphragm and a battery including the diaphragm. The diaphragm of the present invention can have a strong puncture strength while maintaining a high porosity, so that the fast charging performance of the battery is high while its self-discharge and safety performance are not affected, and the surface of the diaphragm is not coated with a coating layer, but it can improve the interface stability between the diaphragm and the positive electrode active layer and the negative electrode active layer, improve the long cycle performance of the battery, and avoid the influence of the coating layer on the fast charging performance of the battery, further improving the fast charging performance of the battery.
[0005] To achieve the above-mentioned purpose, the first aspect of the present invention provides a diaphragm, which includes a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer includes inorganic particles and a first polymer, the ceramic layer is a porous structure, and the porous structure includes pores with a diameter ≥0.5μm. Within a range of 100μm×100μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter ≥0.5μm is 10-800 and the number of the first polymer is 10-500; the diaphragm satisfies the following relationship: 1<D1 / D2<20, wherein D1 is the average diameter of pores with a diameter ≥0.5μm in the ceramic layer, in μm; D2 is the average particle size of the inorganic particles, in μm.
[0006] A second aspect of the present invention provides a battery, comprising the separator according to the first aspect of the present invention.
[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0008] The diaphragm of the present invention can increase the porosity of the diaphragm by controlling the number of pores with a diameter ≥0.5μm, thereby improving the ion conductivity of the diaphragm and further improving the fast charging performance of the battery; by controlling the number of the first polymer, the interface stability between the diaphragm and the positive electrode active layer and the negative electrode active layer can be improved, thereby improving the long cycle performance of the battery, and avoiding the influence of the coating layer on the fast charging performance of the battery, further improving the fast charging performance of the battery; at the same time, by controlling the diaphragm to satisfy the relationship: 1<D1 / D2<20, the diaphragm can have a large number of large pores (for example, pores with a diameter ≥0.5μm), thereby further improving the porosity of the diaphragm and further improving the fast charging performance of the battery, and can also increase the packing density of inorganic particles, thereby improving the thermal stability and puncture strength of the diaphragm, thereby making the diaphragm have both high porosity and high puncture strength, so that the battery has high long cycle performance and high fast charging performance, while self-discharge and safety performance are not affected. In addition, since the diaphragm of the present invention does not include a coating layer, the cost of the diaphragm is greatly reduced.
[0009] Other features and advantages of the present invention will be described in detail in the following detailed description.
[0010] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Shown is a SEM image of a diaphragm in one embodiment of the present invention.
[0012] Figure 2 Shown is a pore size distribution curve of the diaphragm in Example 1 of the present invention.
[0013] Figure 3 Shown is a schematic cross-sectional view of the separator of the present invention.
[0014] Figure 4 FIG. 1 is a schematic top view of the diaphragm of the present invention. DETAILED DESCRIPTION
[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints. Data near the endpoint value (for example, a range of variation less than or equal to ±25% (for example, ±25%, ±20%, ±15%, ±10%, ±5% or ±1%) of the value) also belongs to the protection scope of the data range of the present invention.
[0016] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.
[0017] The first aspect of the present invention provides a diaphragm, which includes a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer includes inorganic particles and a first polymer, the ceramic layer is a porous structure, and the porous structure includes pores with a diameter ≥0.5μm. Within a range of 100μm×100μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter ≥0.5μm is 10-800 and the number of the first polymer is 10-500; the diaphragm satisfies the following relationship: 1<D1 / D2<20, wherein D1 is the average diameter of pores with a diameter ≥0.5μm in the ceramic layer, in μm; D2 is the average particle size of the inorganic particles, in μm.
[0018] Figure 1 is a SEM image of a diaphragm in one embodiment of the present invention, Figure 1 It can be seen that the ceramic layer is a porous structure, and Figure 1 The red circles are pores with a diameter ≥ 0.5 μm. Figure 1 The green circle in the middle is the first polymer, where one red circle represents a hole with a diameter ≥ 0.5 μm, and one green circle represents one first polymer. It should be noted that the red circle only marks Figure 1 The pores with a diameter of ≥0.5 μm do not indicate Figure 1 All pores with a diameter ≥ 0.5 μm in the Figure 1 The first polymer in the middle part does not mean Figure 1 All of the first polymer.
[0019] like Figure 3 and Figure 4 As shown, the diaphragm includes a substrate 1 and a ceramic layer 2 located on both sides of the substrate 1. The ceramic layer includes inorganic particles 23 and a first polymer 21. The ceramic layer is a porous structure, and 22 is the pore of the ceramic layer.
[0020] In the present invention, the term "diameter" and "average diameter" have different meanings. The term "diameter" refers to the diameter of a single pore. For example, a pore with a diameter ≥ 0.5 μm means that the diameter of a single pore is ≥ 0.5 μm; the number of pores with a diameter ≥ 0.5 μm means that the number of pores with a diameter ≥ 0.5 μm. The term "average diameter" refers to the average value of the diameters of all pores in a system. For example, the average diameter of pores with a diameter ≥ 0.5 μm in a ceramic layer means the average value of the diameters of all pores with a diameter ≥ 0.5 μm in a system.
[0021] Both the diameter and the average diameter can be obtained by SEM testing. For example, it can be obtained by testing in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), observe the surface of the ceramic layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the diameter, a square or rectangle with the smallest area that completely surrounds one hole is drawn on the obtained image, that is, a square or rectangle in which the end of the hole is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the diameter of the hole, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the diameter of the hole. For any 81 holes, the diameter of each hole is measured, and the average value of the number is set as the average diameter. It should be noted that when more than 81 holes are observed in the captured image, the number average of any 81 holes in the image is set as the average diameter of the holes. When 81 holes are not observed in the image, multiple images are captured and the number average of the total 81 holes is set as the average diameter.
[0022] In the present invention, the term "average particle size" refers to the average value of the diameters of all particles in a system. The average particle size can be measured in the following manner: using an electrolytic emission scanning electron microscope (S-3400N manufactured by Hitachi, Ltd.), observe the surface of the porous layer at a magnification of 50,000 times. The image size at this time is 2.5μm×1.8μm. It should be noted that the number of pixels is 1,280 pixels×960 pixels, and the size of 1 pixel is 2nm×1.9nm. For the average particle size, a square or rectangle with the smallest area that completely surrounds one particle is drawn on the obtained image, that is, a square or rectangle in which the end of the particle is connected to the four sides of the square or rectangle. In the case of a square, the length of one side is set as the particle size, and in the case of a rectangle, the length of the long side (major axis diameter) is set as the particle size. For any 81 particles, measure their respective particle sizes, and set their number average as the average particle size. It should be noted that when more than 81 particles are observed in the captured image, the number average of any 81 particle sizes in the image is set as the average particle size. When 81 particles are not observed in the image, multiple images are captured and the number average of the total 81 particle sizes is set as the average particle size.
[0023] The ceramic layer in the diaphragm of the present invention is a porous structure, and the porous structure includes pores with a diameter of ≥0.5 μm, and the number of pores with a diameter of ≥0.5 μm in a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer is 10-800 (for example, 10, 50, 100, 200, 300, 400, 500, 600, 700 or 800). By controlling the number of pores with a diameter of ≥0.5 μm and pores with a diameter of ≥0.5 μm in the porous structure, a large number of pores can be present on the surface or inner layer of the ceramic layer of the diaphragm, thereby improving the porosity of the diaphragm, improving the ion conduction performance of the diaphragm, and thereby improving the fast charging performance of the battery. Performance; by controlling the ratio of the average diameter (D1) of pores with a diameter ≥ 0.5 μm in the ceramic layer to the average particle size (D2) of the inorganic particles so as to satisfy the relationship 1<D1 / D2<20 (for example, 1.1, 3, 5, 8, 10, 13, 15, 18 or 19.9), on the one hand, a large number of pores can be present in the diaphragm, further improving the porosity of the diaphragm, thereby further improving the ion transmission performance of the diaphragm and further improving the fast charging performance of the battery; on the other hand, the packing density between the inorganic particles can be increased, thereby improving the puncture strength and thermal stability of the diaphragm, thereby reducing the self-discharge of the battery, improving the safety performance of the battery, and making the self-discharge and safety performance of the battery unaffected. When D1 / D2≤1, the packing density between the inorganic particles is too low, the thermal stability of the diaphragm is poor, and the safety performance of the battery is low; when D1 / D2≥20, the pore size is too large, the thermal stability of the diaphragm is poor, and the safety performance of the battery is low. The ceramic layer of the separator of the present invention includes a first polymer, which is a particle with adhesive properties. By controlling the number of the first polymer in the range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer to 10-500 (for example, 10, 50, 100, 200, 300, 400 or 500), the interface between the separator and the positive electrode active layer and the negative electrode active layer can have a higher stability, thereby improving the long cycle performance of the battery. Moreover, since the first polymer is a particle with adhesive properties, the separator of the present invention does not need to be coated with a coating layer separately, reducing the adverse effect of the coating layer on the fast charging performance of the battery. Therefore, the separator of the present invention has the advantages of higher long cycle performance and higher fast charging performance while having lower self-discharge and higher safety.
[0024] In the present invention, by controlling the number of pores with a diameter ≥ 0.5 μm, the number of the first polymer, and the ratio of the average diameter (D1) of pores with a diameter ≥ 0.5 μm in the ceramic layer to the average particle size (D2) of the inorganic particles, the battery can have higher fast charging performance and higher long cycle performance compared with the prior art. In order to further improve the effect, one or more of the technical features can be further optimized.
[0025] In one example, 2≤D1 / D2≤15.
[0026] In one example, D1 is 0.5 μm-10 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0027] In one example, D1 is 2 μm-8 μm.
[0028] In one example, D2 is 0.1 μm-3 μm (eg, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, or 3 μm).
[0029] In one example, D2 is 0.5 μm-2 μm.
[0030] In one example, the number of holes with a diameter of ≥0.5 μm in an area of 100 μm×100 μm randomly selected on the surface of the ceramic layer is 50-500.
[0031] In one example, within an arbitrarily selected area of 100 μm×100 μm on the surface of the ceramic layer, the number of the first polymers is 30-300.
[0032] According to a specific embodiment, 2≤D1 / D2≤15, D1 is 2μm-8μm, D2 is 0.5μm-2μm, and within a 100μm×100μm range arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter ≥0.5μm is 50-500 and the number of the first polymers is 30-300.
[0033] In one example, the diaphragm satisfies the following relationship: 1≤D3 / H1≤5 (for example, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5), wherein D3 is the average particle size of the first polymer in the ceramic layer, in μm; H1 is the thickness of the ceramic layer, in μm.
[0034] Controlling D3 / H1 within the above range can make the size of the first polymer protruding on the surface of the ceramic layer more suitable. On the one hand, it can make the ceramic layer have better adhesion, so that the diaphragm has a higher interface stability with the positive active layer and the negative active layer, and further improve the long cycle performance of the battery; on the other hand, it can make the distance between the ceramic layer and the positive active layer and the negative active layer maintain a more suitable size, so that the diaphragm has a good interface distance with the positive active layer and the negative active layer, thereby improving the fast charging and long cycle performance of the battery. When D3 / H1<2, due to the small average particle size of the first polymer, there is not enough first polymer to maintain good contact with the positive active layer and the negative active layer, thereby affecting the interface adhesion between the diaphragm and the positive active layer and the negative active layer, and the fast charging and long cycle performance of the battery cannot be effectively improved; when D3 / H1>5, due to the large average particle size of the first polymer, the size of the first polymer protruding on the surface of the ceramic layer is too large, thereby making the distance between the diaphragm and the positive active layer and the negative active layer too large, affecting the interface stability between the diaphragm and the positive active layer and the negative active layer, and the fast charging and long cycle performance of the battery cannot be effectively improved.
[0035] It is understandable that in the process of preparing the diaphragm, the thickness of the ceramic layer cannot be absolutely uniform, so in the present invention, the thickness H1 of the ceramic layer is the maximum thickness of the ceramic layer. The thickness of the ceramic layer can be obtained by SEM testing.
[0036] In one example, 1.5≤D3 / H1≤4.
[0037] In one example, D3 is 2 μm-10 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm).
[0038] In one example, D3 is 3 μm-6 μm.
[0039] In one example, H1 is 1 μm-5 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm).
[0040] In one example, H1 is 1.5 μm-3 μm.
[0041] According to a specific implementation, D3 is 3 μm-6 μm, H1 is 1.5 μm-3 μm, and the diaphragm satisfies the following relationship: 1.5≤D3 / H1≤4.
[0042] According to a specific implementation, D1 is 2 μm-8 μm, D2 is 0.5 μm-2 μm, D3 is 3 μm-6 μm, H1 is 1.5 μm-3 μm, and the diaphragm satisfies the following relationships: 2≤D1 / D2≤15 and 2≤D3 / H1≤5.
[0043] In one example, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 20%-70% (for example, 20%, 30%, 40%, 50%, 60% or 70%). Controlling the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer within the above range can, on the one hand, make the diaphragm have good heat resistance, thereby improving the safety performance of the battery; on the other hand, it can increase the porosity of the diaphragm, so that the diaphragm has good ion permeability, thereby improving the fast charging and long cycle performance of the battery. When the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer accounts for less than 20%, the porosity of the diaphragm is low, so that the ion permeability of the diaphragm is insufficient, and the fast charging and long cycle performance of the battery cannot be effectively improved; when the volume of pores with a diameter of ≥0.5 μm in the total volume of the pores in the ceramic layer accounts for more than 70%, the heat resistance of the diaphragm is low, and the safety performance of the battery cannot be guaranteed.
[0044] In the present invention, the volume ratio of pores with a diameter of ≥0.5 μm in the total volume of pores in the ceramic layer can be obtained by testing in the following manner: For example, a mercury intrusion test method can be used, specifically, a mercury intrusion test method can be used to obtain a pore size distribution curve of the entire diaphragm (such as Figure 2 As shown in the figure), the pore size of the substrate layer in the diaphragm does not exceed 0.08μm. Therefore, the pore size distribution curve of the ceramic layer can be obtained by eliminating the pore sizes ≤0.08μm in the pore size distribution curve of the diaphragm in the pore size distribution curve of the entire diaphragm. The ratio of the integral area of pores greater than or equal to 0.5μm in the pore size distribution curve of the ceramic layer to the total integral area of the pore size distribution curve of the ceramic layer is calculated, which is the volume proportion of pores with a diameter ≥0.5μm in the total volume of pores in the ceramic layer.
[0045] In one example, based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 30%-60%.
[0046] In one example, the coverage of the first polymer on the surface of the ceramic layer is 5%-25% (for example, 5%, 10%, 15%, 20% or 25%). Controlling the coverage of the first polymer on the surface of the ceramic layer within the above range can, on the one hand, make the ceramic layer have better adhesion, so that the diaphragm has higher interface stability with the positive electrode active layer and the negative electrode active layer, further improving the long cycle performance of the battery; on the other hand, it can keep the distance between the ceramic layer and the positive electrode active layer and the negative electrode active layer at a more appropriate size, so that the diaphragm has a good interface distance with the positive electrode active layer and the negative electrode active layer, thereby improving the fast charging and long cycle performance of the battery. When the coverage rate of the first polymer on the surface of the ceramic layer is lower than 5%, due to the low coverage rate of the first polymer, the ceramic layer does not have sufficient first polymer to maintain good contact with the positive electrode active layer and the negative electrode active layer, thereby affecting the interface adhesion between the diaphragm and the positive electrode active layer and the negative electrode active layer, and failing to effectively improve the fast charging and long cycle performance of the battery; when the coverage rate of the first polymer on the surface of the ceramic layer is higher than 25%, due to the excessive number of first polymer particles and the excessively high coverage rate, the ion conductivity is affected, and failing to effectively improve the fast charging and long cycle performance of the battery.
[0047] In one example, the coverage of the first polymer on the surface of the ceramic layer is 8%-20%.
[0048] In the present invention, the coverage of the first polymer on the surface of the ceramic layer represents the ratio of the orthographic projection area of the first polymer on the surface of the ceramic layer on the surface of the substrate to the orthographic projection area of the ceramic layer on the surface of the substrate.
[0049] In the present invention, the coverage of the first polymer on the surface of the ceramic layer can be obtained by testing in the following manner: for example, by using a scanning electron microscope (SEM) to test, specifically: using SEM to obtain a microscopic image of the surface of the ceramic layer, randomly dividing an area of 100 μm in the image 2 An area (for example, 100µm×100µm) is divided into uniform squares of 100*100. If the area covered by the first polymer in the square exceeds half of the area of the square, it means that the square is occupied by the first polymer. Otherwise, it means that the square is not occupied by the first polymer. By counting the number of squares occupied by the first polymer, the total number of squares occupied by the first polymer is recorded as X, then the coverage rate = (X / 100*100)*100%. Repeat the above operation 5 times, and the average value of the 5 times is the coverage rate of the first polymer on the surface of the ceramic layer.
[0050] In one example, within an arbitrarily selected range of 100 μm×100 μm on the surface of the ceramic layer, the number of the first polymers is 30-300, and the coverage of the first polymer on the surface of the ceramic layer is 8%-20%.
[0051] In one example, based on the total volume of the pores in the ceramic layer, the volume of the pores with a diameter ≥ 0.5 μm accounts for 30%-60%, and the coverage of the first polymer on the surface of the ceramic layer is 8%-20%.
[0052] In one example, the ceramic layer further includes a membrane binder and a thickener.
[0053] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 75%-98% (for example, 75%, 80%, 85%, 90%, 95% or 98%), the weight content of the first polymer is 1%-18% (for example, 1%, 5%, 10%, 15% or 18%), the weight content of the diaphragm binder is 0.5%-8% (for example, 0.5%, 1%, 3%, 5% or 8%), and the weight content of the thickener is 0.4%-4% (for example, 0.4%, 1%, 2%, 3% or 4%).
[0054] In one example, the inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride.
[0055] In one example, the first polymer includes a first monomer and a second monomer and optionally ("optionally" means that it may or may not exist) a third monomer. The first polymer has adhesive properties and can replace the coating layer to improve the stability between the separator and the positive electrode active layer and the negative electrode active layer.
[0056] In one example, the first monomer includes one or more of an acrylonitrile monomer, a styrene monomer, and an acrylate monomer.
[0057] In one example, the acrylic acid ester monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.
[0058] In one example, the styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.
[0059] In one example, the acrylonitrile monomer includes one or more of acrylonitrile, triphenylacrylonitrile, 3-cyclopentylacrylonitrile and 3,3-(diphenyl)acrylonitrile.
[0060] In one example, the second monomer includes one or more of dimethyl acrylamide, diethyl acrylamide, divinyl benzene, trimethylol propane triacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, triethylene glycol dimethacrylate, and tetraethylene glycol dimethacrylate.
[0061] In one example, the third monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate, and allyl glycidyl ester.
[0062] In one example, the substrate includes one or more of polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyparaphenylene, polynaphthalene, polyimide, polyamide, aramid, and polyparaphenylenebenzodithiazole.
[0063] The diaphragm of the present invention can be prepared by the following method:
[0064] Inorganic particles, water or deionized water, a thickener and a membrane binder are mixed to prepare an aqueous slurry, an initial first polymer and a second polymer are added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on one side or both sides of the substrate to prepare an initial membrane. The initial membrane includes a substrate and a ceramic layer located on one side or both sides of the substrate, and the ceramic layer includes inorganic particles, an initial first polymer and a second polymer.
[0065] The initial separator is assembled with a positive electrode sheet, a negative electrode sheet and an electrolyte to form a battery, and the battery is hot pressed (hot pressing conditions: hot pressing temperature is 60°C-90°C (for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C), hot pressing pressure is 0.1MPa-1.5MPa (for example, 0.1MPa, 0.3MPa, 0.5MPa, 0.8MPa, 1MPa, 1.3MPa or 1.5MPa), hot pressing time is 10min-60min (10min, 20min, 30min, 40min, 50min or 60min)), after hot pressing, since the initial first polymer is partially dissolved and the second polymer is completely dissolved, the first polymer exists in the ceramic layer of the separator, the second polymer does not exist, and the first polymer existing in the ceramic layer is the partially undissolved initial first polymer. The partially dissolved initial first polymer and the completely dissolved second polymer form a large number of pores in the middle and on the surface of the ceramic layer, thereby obtaining the separator comprising a large number of pores of the present invention. It is understood that the initial first polymer is of the same type as the first polymer in the ceramic layer, but the average particle size of the initial first polymer is different from the average particle size of the first polymer. In the process of preparing a battery, hot pressing is an indispensable step in preparing a battery, which may also be referred to as formation in the art.
[0066] In one example, the thickener includes one or more of methyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), and lithium carboxymethyl cellulose (CMC-Li).
[0067] In one example, the membrane binder includes one or more of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyimide, polyacrylonitrile, polymethyl (meth)acrylate, aramid resin, poly (meth)acrylic acid, styrene-butadiene rubber (SBR), polyvinyl alcohol, polyvinyl acetate and carboxyethyl cellulose.
[0068] In one example, the initial first polymer includes a first monomer and a second monomer and optionally ("optionally" means that it may or may not be present) a third monomer.
[0069] In one example, the second polymer includes a fourth monomer and a fifth monomer.
[0070] In one example, the fourth monomer includes one or more of an acrylonitrile monomer, a styrene monomer, and an acrylate monomer.
[0071] In one example, the acrylic acid ester monomer includes one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate.
[0072] In one example, the styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.
[0073] In one example, the acrylonitrile monomer includes one or more of acrylonitrile, triphenylacrylonitrile, 3-cyclopentylacrylonitrile and 3,3-(diphenyl)acrylonitrile.
[0074] In one example, the fifth monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate, and allyl glycidyl ester.
[0075] In one example, the weight ratio of the inorganic particles, the thickener, and the membrane binder is (85%-98%): (1%-5%): (1%-10%).
[0076] In one example, the weight ratio of the initial first polymer, the weight of the second polymer and the weight of the inorganic particles is (1%-15%): (1%-15%): (98%-70%). It is understood that the weight content of the first polymer can be in the range of 1%-15% (e.g., 1%, 5%, 10% or 155), the weight content of the second polymer can be in the range of 1%-15% (e.g., 1%, 5%, 10% or 155), and the weight content of the inorganic particles can be in the range of 98%-70% (e.g., 98%, 95%, 90%, 85%, 80%, 75% or 70%).
[0077] In one example, the average particle size of the initial first polymer is 2 μm-10 μm (eg, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm).
[0078] In one example, the average particle size of the initial first polymer is 3 μm-6 μm.
[0079] In one example, the average particle size of the second polymer is 0.5 μm-5 μm (eg, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm).
[0080] In one example, the average particle size of the second polymer is 1 μm-4 μm.
[0081] A second aspect of the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the separator is the separator described in the first aspect of the present invention.
[0082] Since the battery of the present invention includes the diaphragm described in the first aspect, the fast charging performance and long cycle performance of the battery are improved.
[0083] In one example, the battery is a lithium-ion secondary battery.
[0084] In one example, the electrolyte includes an organic solvent, and the organic solvent includes a first organic solvent and a second organic solvent.
[0085] In one example, the first organic solvent includes one or more of dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), propyl propionate (PP), ethyl propionate (EP) and ethyl acetate (EA).
[0086] In one example, the second organic solvent is propylene carbonate (PC) and / or ethylene carbonate (EC).
[0087] In one example, the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is (0.05-20):1 (for example, 0.05, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20). Controlling the weight ratio of the first organic solvent to the weight ratio of the second organic solvent within the above range can make the electrolyte have a suitable viscosity and good ionic conductivity, so that the battery has a higher long cycle performance and better fast charging performance. When the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is lower than 0.05:1, the content of the second organic solvent is too high, resulting in too high viscosity of the electrolyte, which reduces the fast charging performance of the battery; when the weight ratio of the first organic solvent to the weight ratio of the second organic solvent is higher than 20:1, the content of the first organic solvent is too high, resulting in low ionic conductivity, which reduces the long cycle performance of the battery.
[0088] In one example, the weight ratio of the first organic solvent to the second organic solvent is (0.1-10):1.
[0089] In one example, the organic solvent includes ethyl methyl carbonate (EMC), ethyl acetate (EA) and ethylene carbonate (EC).
[0090] In one example, the weight ratio of ethyl methyl carbonate (EMC), ethyl acetate (EA) and ethylene carbonate (EC) in the organic solvent is (10%-70%): (10%-70%): (15%-40%). It is understood that the weight content of ethyl methyl carbonate in the organic solvent can be in the range of 10%-70% (e.g., 10%, 20%, 30%, 40%, 50%, 60% or 70%), the weight content of ethyl acetate in the organic solvent can be in the range of 10%-70% (e.g., 10%, 20%, 30%, 40%, 50%, 60% or 70%), and the weight content of ethylene carbonate in the organic solvent can be in the range of 15%-40% (e.g., 15%, 20%, 25%, 30%, 35% or 40%), but it needs to be satisfied that the sum of the weight content of ethyl methyl carbonate, the weight content of ethyl acetate and the weight content of ethylene carbonate in the organic solvent is 100%.
[0091] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 70%-86% (eg, 70%, 73%, 75%, 78%, 80%, 85% or 86%).
[0092] In one example, based on the total weight of the electrolyte, the weight content of the organic solvent is 75%-81%.
[0093] In one example, the electrolyte further includes LiFSI and optionally an additive.
[0094] In one example, the additives include fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), vinylene carbonate (VC), lithium difluorophosphate (LiPO 2 F 2 ), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate (LiODFP), lithium tetrafluoroborate (LiBF 4 ) and lithium tetrafluorooxalophosphate (LiTFOP) one or more.
[0095] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20% (e.g., 2%, 5%, 10%, 15% or 20%), and the weight content of the additive is 0%-10%. When the weight content of the additive in the electrolyte is 0%, it means that there is no additive in the electrolyte.
[0096] In one example, based on the total weight of the electrolyte, the weight content of LiFSI is 3%-9%, and the weight content of the additive is 1%-8%.
[0097] In one example, the electrolyte further includes a lithium salt.
[0098] In one example, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium perchlorate.
[0099] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 12%-30% (eg, 12%, 15%, 18%, 20%, 22%, 25%, 28% or 30%).
[0100] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 15%-25%.
[0101] In one example, at 60°C-90°C, the first polymer is immersed in a solvent for 2min-10min, and the solubility of the first polymer is ≤50% (for example, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 1%, 0.5%, 0.1%). Controlling the solubility of the first polymer within the above range can make the ceramic layer have better adhesion, so that the diaphragm has higher interface stability with the positive electrode active layer and the negative electrode active layer, further improving the long cycle performance of the battery. When the solubility of the first polymer is higher than 50%, after the battery is hot-pressed, the amount of the first polymer retained in the ceramic layer is small, resulting in insufficient first polymer to maintain good contact with the positive electrode active layer and the negative electrode active layer, thereby affecting the interface adhesion between the diaphragm and the positive electrode active layer and the negative electrode active layer, and failing to effectively improve the fast charge and long cycle performance of the battery.
[0102] The solvent may be the organic solvent described in the present invention, or may be the electrolyte solution comprising the organic solvent described in the present invention.
[0103] In one example, at 60° C.-90° C., the first polymer is immersed in the solvent for 2 min-10 min, and the solubility of the first polymer is 1%-20%.
[0104] In the present invention, the solubility can be tested by the following method: taking EMC as the solvent, take a first polymer with a weight of M1, add it to an EMC beaker with a content of 20*M1, place the beaker in an oven at 80°C for 10 minutes, take out the remaining first polymer and dry it, weigh the remaining first polymer and record the weight as M2, then the solubility of the first polymer in the solvent EMC is (M1-M2) / M1*100%.
[0105] In one example, the second polymer is completely dissolved when immersed in the solvent at 60°C-90°C for 2min-10min. Due to this characteristic of the second polymer, the second polymer is completely dissolved during the battery hot pressing process and forms a large number of pores in the ceramic layer of the separator.
[0106] The battery may further include a positive electrode sheet and a negative electrode sheet.
[0107] The positive electrode sheet may be a conventional positive electrode sheet in the art. For example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer located on at least one surface of the positive electrode current collector.
[0108] There is no special restriction on the positive electrode active layer, and the positive electrode active layer may include components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. according to the conventional composition in the art. Among them, the components such as positive electrode active material, positive electrode conductive agent, positive electrode binder, etc. may be selected from conventional materials in the art, for example, the positive electrode active material may be selected from one or more of lithium nickel oxide, lithium titanate, lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, and lithium manganese oxide; the positive electrode conductive agent may be selected from one or more of acetylene black, conductive carbon black, carbon nanotubes, conductive graphite, and graphene; the positive electrode binder may be selected from one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, styrene-butadiene rubber, and styrene-acrylic rubber.
[0109] In one example, the positive electrode active material is selected from lithium iron phosphate or lithium iron phosphate doped and coated with two or more elements of Al, Mg, Mn, Cr, Ti, Zr, and V.
[0110] In one example, based on the total weight of the positive electrode active layer, the weight content of the positive electrode active material is 90%-98% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the positive electrode conductor is 0.5%-5% (for example, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the positive electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%).
[0111] The negative electrode sheet can be a conventional negative electrode sheet in the art, for example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer coated on one side or both sides of the negative electrode current collector, and the negative electrode active layer includes a negative electrode active material, a negative electrode conductive agent and a negative electrode binder; the negative electrode active material can adopt negative electrode active materials for batteries known in the art, such as one or more of carbon-based materials, silicon-based materials, tin-based materials, and titanium-based materials; specifically, it can be one or more of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds (such as SiOx / C), silicon-carbon composites (such as Si / C), silicon-nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys.
[0112] According to a specific embodiment, the negative electrode active material is selected from one or more of artificial graphite, hard carbon, SiOx / C and Si / C.
[0113] In one example, the negative electrode conductive agent is one or more of conductive carbon black, carbon nanotubes (eg, single-walled carbon nanotubes and multi-walled carbon nanotubes), conductive graphite, and graphene.
[0114] In one example, the negative electrode binder is one or more of polyvinylidene fluoride (PVDF), acrylic acid-modified PVDF, polyacrylate polymers, polytetrafluoroethylene, perfluorosulfonic acid ionomers, polyacrylonitrile, polyimide, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR) and styrene-acrylic rubber.
[0115] In one example, based on the total weight of the negative electrode active layer, the weight content of the negative electrode active material is 90%-98% (for example, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the negative electrode conductive agent is 0%-5% (for example, 0%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%), and the weight content of the negative electrode binder is 1%-5% (for example, 1%, 2%, 3%, 4% or 5%). When the weight content of the negative electrode conductive agent in the negative electrode active material layer is 0%, it means that there is no negative electrode conductive agent in the negative electrode active material layer.
[0116] The battery of the present invention has high long cycle performance and good fast charging performance.
[0117] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0118] The following examples are provided to illustrate the separator and battery of the present invention.
[0119] Example 1
[0120] (1) Preparation of diaphragm
[0121] Component preparation: Substrate: polyethylene, thickness 9 μm;
[0122] Ceramic layer: inorganic particles: aluminum oxide; thickener: sodium carboxymethyl cellulose; diaphragm binder: poly(meth)acrylic acid; initial first polymer: polymethyl methacrylate; second polymer: polymethyl methacrylate; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%; the weight ratio of the initial first polymer, the second polymer and the inorganic particles is 7%:7%:86%.
[0123] Inorganic particles, water, a thickener and a membrane binder are mixed to prepare an aqueous slurry (with a solid content of 28%), a first polymer and a second polymer are added to the aqueous slurry to prepare a ceramic slurry, and the ceramic slurry is coated on both sides of a substrate to prepare an initial membrane.
[0124] (2) Preparation of electrolyte
[0125] Ingredients preparation: Lithium salt: lithium hexafluorophosphate, 12.5 parts by weight;
[0126] Organic solvent: 76.5 parts by weight, wherein the weight ratio of ethyl methyl carbonate (EMC), ethyl acetate (EA) and ethylene carbonate (EC) is 35%:35%:30%;
[0127] LiFSi, 6.5 parts by weight;
[0128] Additives: vinylene carbonate (VC), 4.5 parts by weight;
[0129] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), the organic solvents were mixed evenly to obtain a mixed solution 1, additives were added to the mixed solution 1 to obtain a mixed solution 2, LiFSi and lithium salt were slowly added to the mixed solution 2, and the mixture was stirred evenly to obtain a non-aqueous electrolyte.
[0130] (3) Preparation of positive electrode
[0131] The positive electrode active material (lithium iron phosphate (LFP) doped with titanium and vanadium), the positive electrode binder (polyvinylidene fluoride (PVDF)), and the positive electrode conductive agent (acetylene black) are mixed in a weight ratio of 96.5:1.5:2.0, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity; the positive electrode slurry is evenly coated on the surface of both sides of an aluminum foil with a thickness of 10 μm; the coated aluminum foil is baked in an oven with 5 different temperature gradients (95℃±5℃, 100℃±5℃, 103℃±5℃, 100℃±5℃, 95℃±5℃), and then dried in an oven at 120℃ for 8 hours, and then rolled and cut to obtain the required positive electrode sheet.
[0132] (4) Preparation of negative electrode
[0133] The negative electrode active material (artificial graphite), the negative electrode conductive agent (including 0.2 parts by weight of single-walled carbon nanotubes (SWCNT) and 1 part by weight of conductive carbon black (SP)), and the negative electrode binder (including 1 part by weight of sodium carboxymethyl cellulose (CMC-Na) and 2.5 parts by weight of styrene-butadiene rubber (SBR)) are mixed in a weight ratio of 95.3:1.2:3.5, and a slurry is prepared by a wet process (water is added to the mixture formed by the above mixing, and the mixture is stirred under the action of a vacuum stirrer until the mixture becomes a negative electrode slurry with uniform fluidity), and the slurry is coated on the surfaces of both sides of the negative electrode current collector (copper foil), and the negative electrode sheet is obtained by drying (temperature: 85°C, time: 5h), rolling and die-cutting.
[0134] (5) Preparation of lithium-ion secondary batteries
[0135] The positive electrode sheet of step (3), the separator of step (1), and the negative electrode sheet of step (4) are wound to obtain a bare cell without liquid injection, and 5MPa is applied to the wound core for 10 minutes; the bare cell is placed in an outer packaging foil, and the electrolyte of step (2) is injected into the dried bare cell, and the process includes vacuum packaging, standing, hot pressing (wherein the hot pressing temperature is 80°C, the hot pressing pressure is 1MPa, and the hot pressing time is 40 minutes. After hot pressing, the first polymer in the initial separator is partially dissolved, and the second polymer is completely dissolved. The partially dissolved first polymer and the completely dissolved second polymer form a large number of pores in the middle and surface of the ceramic layer of the separator to obtain the separator of the present invention), shaping, sorting, etc., to obtain the desired lithium ion secondary battery. Wherein, the separator after hot pressing, based on the total weight of the ceramic layer, has an inorganic particle weight content of 85.6%, a first polymer weight content of 6.9%, a separator binder weight content of 4.7%, and a thickener weight content of 2.8%.
[0136] Example 2
[0137] The method is carried out in accordance with Example 1, except that the weight of the organic solvent remains unchanged, and the organic solvent is adjusted to consist of a first organic solvent (EMC) and a second organic solvent (EC), wherein the weight ratio of the first organic solvent to the second organic solvent is 1:1.
[0138] Example 3 Group
[0139] This group of embodiments is used to illustrate that different combinations of parameter values can still achieve the effects of the present invention.
[0140] This example group was carried out with reference to Example 1, and specifically see Table 1-1 and Table 1-2.
[0141] Example 4
[0142] This embodiment is used to illustrate that different parameter value combinations can still achieve the effects of the present invention.
[0143] Refer to Example 2, and see Table 1-1 and Table 1-2 for details.
[0144] Example 5 Group
[0145] This group of embodiments is used to illustrate the impact caused by changes in D1 / D2.
[0146] This embodiment group is carried out with reference to embodiment 1, except that D1 / D2 is changed, see Table 1-1 and Table 1-2 for details.
[0147] Example 6 Group
[0148] This group of examples is used to illustrate the impact produced when D3 / H1 changes.
[0149] This example group is carried out with reference to Example 1, except that D3 / H1 is changed, as shown in Table 1-1 and Table 1-2 for details.
[0150] Example 7 Group
[0151] This set of examples is used to illustrate the effects of changing the specific selection of the first polymer.
[0152] This example group is carried out with reference to Example 1, except that the first polymer is changed, as shown in Table 1-1 and Table 1-2 for details.
[0153] Example 8 Group
[0154] This set of examples is used to illustrate the effects of changing the specific selection of the second polymer.
[0155] This example group is carried out with reference to Example 1, except that the second polymer is changed, as shown in Table 1-1 and Table 1-2 for details.
[0156] Example 9 Group
[0157] This group of examples is used to illustrate the impact of changing the weight ratio of EMC / EA / EC.
[0158] This example group was carried out with reference to Example 1, except that the weight ratio of EMC / EA / EC was changed, as shown in Table 1-1 and Table 1-2 for details.
[0159] Example 10 Group
[0160] This group of examples is used to illustrate the influence produced when the weight ratio of the first organic solvent to the second organic solvent is changed.
[0161] This example group was carried out with reference to Example 2, except that the weight ratio of the first organic solvent to the second organic solvent was changed, as shown in Table 1-1 and Table 1-2 for details.
[0162] Example 11 Group
[0163] This group of embodiments is used to illustrate the impact produced when the coverage of the first polymer on the surface of the ceramic layer changes.
[0164] This embodiment group is carried out with reference to embodiment 1, except that the coverage of the first polymer on the surface of the ceramic layer is changed by adjusting the ratio of the initial weight of the first polymer, the weight of the second polymer and the weight of the inorganic particles, see Table 1-1 and Table 1-2 for details.
[0165] Example 12 Group
[0166] This group of embodiments is used to illustrate the impact produced when the volume percentage of pores with a diameter ≥ 0.5 μm in the ceramic layer changes.
[0167] This example group is carried out with reference to Example 1, except that the volume proportion of pores with a diameter ≥ 0.5 μm in the ceramic layer is changed by adjusting the ratio of the initial weight of the first polymer, the weight of the second polymer and the weight of the inorganic particles, as shown in Table 1-1 and Table 1-2 for details.
[0168] Comparative Example 1
[0169] Component preparation: Substrate: polyethylene, thickness 9 μm;
[0170] Ceramic layer: inorganic particles: alumina; thickener: sodium carboxymethyl cellulose; diaphragm binder: poly (meth) acrylic acid; wherein the weight ratio of the inorganic particles, the thickener and the diaphragm binder is 92%:3%:5%.
[0171] Inorganic particles, water, a thickener and a separator binder are mixed to prepare an aqueous slurry (with a solid content of 28%), and the aqueous slurry is coated on both sides of the substrate.
[0172] Comparative Example 2
[0173] The same is carried out as in Example 1, except that D1 / D2<1. For details, see Table 1-1 and Table 1-2.
[0174] Comparative Example 3
[0175] The same procedure is carried out as in Example 1, except that D1 / D2>20. For details, see Table 1-1 and Table 1-2.
[0176] Table 1-1
[0177]
[0178]
[0179] *Same as Example 1.
[0180] Table 1-2
[0181]
[0182] *Same as Example 1.
[0183] Test Case
[0184] The diaphragms and lithium-ion secondary batteries obtained in the examples and comparative examples were tested as follows:
[0185] (1) Diaphragm shrinkage test
[0186] Take a diaphragm sample of 15cm*15cm length, pierce two holes with a diameter of 0.5mm at an interval of 10cm along the length direction of the diaphragm, and bake the sample in an oven at 150±2℃ for 1h. The distance between the two holes before baking is L1, and the distance between the two holes after baking is L2. Thermal shrinkage = (L1-L2) / L1*100%.
[0187] (2) 150℃ furnace temperature test
[0188] The lithium-ion secondary battery is heated in a convection air box at a starting temperature of (25±3)°C, a temperature change rate of (5±2)°C / min, and the temperature is raised to (150±2)°C. The test is terminated after maintaining for 60 minutes and the battery status is recorded. For each sample of 30 batteries, if no explosion and / or fire occurs, it is indicated as "passed", and if explosion or fire occurs, it is indicated as "failed". The result is expressed as "number of passes / 30", for example, "30 / 30" means that all batteries passed, and "10 / 30" means that 10 batteries out of 30 batteries failed.
[0189] (3) Long cycle test
[0190] Place the lithium-ion secondary battery in a (25±2)℃ environment and let it stand for 2-3 hours. When the battery body reaches (25±2)℃, charge the battery at 3C constant current with a cutoff current of 0.05C. After the battery is fully charged (100% SOC), let it sit for 5 minutes, and then discharge it at 3C constant current to a cutoff voltage of 2.2V. Record the highest discharge capacity of the first three cycles as the initial capacity Q. When the cycle reaches 2000 times, record the last discharge capacity of the battery Q1. Capacity retention rate (%) = Q1 / Q×100%.
[0191] (4) Fast charging performance test
[0192] Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge it at 0.5C to 2.2V, charge it at 0.5C to the upper limit voltage (3.65V), and record the cell capacity Q2; discharge the fully charged cell at 1C constant current to 2.2V at 25℃±2℃, place it at 25℃ for 4h; charge it at 5C constant current to the upper limit voltage (3.65V), place it at room temperature for 2h, and record the cell capacity Q3. Capacity retention rate = Q3 / Q2*100%
[0193] (5) K value test
[0194] Place the lithium-ion secondary battery at 25℃±2℃ for 4h, discharge at 0.5C to 2.2V, charge at 0.5C to 3.65V, place at 45℃±2℃ for 48h, record the voltage V1, then place at 25±2℃ for 72h, record the voltage V2, K value = (V1-V2) / 72, in mV / h.
[0195] The specific results are recorded in Table 2.
[0196] Table 2
[0197]
[0198]
[0199] It can be seen from Table 2 that the thermal shrinkage rate of the diaphragm of the embodiment is lower than that of the comparative example and the embodiment, the furnace temperature test result of the battery made of the diaphragm of the embodiment is better, the cycle capacity retention rate is significantly improved, the 5C discharge capacity retention rate is significantly improved, and the K value remains basically unchanged, indicating that the diaphragm of the present invention and the battery including the diaphragm improve the long cycle performance and fast charging performance of the battery without affecting the self-discharge and safety performance of the battery by controlling the number of pores with a diameter ≥ 0.5 μm, the number of the first polymer, and the ratio of the average diameter (D1) of pores with a diameter ≥ 0.5 μm in the ceramic layer to the average particle size (D2) of the inorganic particles.
[0200] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A diaphragm, characterized in that: The diaphragm comprises a substrate and a ceramic layer located on one side or both sides of the substrate, the ceramic layer comprises inorganic particles and first polymer particles, the ceramic layer is a porous structure, the porous structure comprises pores with a diameter of ≥0.5 μm, and within a range of 100 μm×100 μm arbitrarily selected on the surface of the ceramic layer, the number of pores with a diameter of ≥0.5 μm is 10-800 and the number of the first polymer particles is 10-500; the diaphragm satisfies the following relationship: 1<D1 / D2<20, wherein D1 is the average diameter of pores with a diameter of ≥0.5 μm in the ceramic layer, in μm; D2 is the average particle size of the inorganic particles, in μm; The first polymer particles are composed of a first polymer, the first polymer includes a first monomer and a second monomer, the first monomer includes one or more of acrylonitrile monomers, styrene monomers and acrylate monomers; the second monomer includes one or more of dimethyl acrylamide, diethyl acrylamide, divinyl benzene, trimethylolpropane triacrylate, ethylene glycol dimethacrylate, ethylene glycol diacrylate, triethylene glycol dimethacrylate and tetraethylene glycol dimethacrylate; Among them, on the image obtained by SEM scanning, a square or rectangle with the smallest area that completely surrounds one hole is depicted, the length of one side of the square or the length of the long side of the rectangle is the diameter of the hole, and the number average of the diameters of any 81 holes is the average diameter of the hole; on the image obtained by SEM scanning, a square or rectangle with the smallest area that completely surrounds one inorganic particle is depicted, the length of one side of the square or the length of the long side of the rectangle is the particle size of the inorganic particle, and the number average of the particle sizes of any 81 inorganic particles is the average particle size of the inorganic particles. On the image obtained by SEM scanning, the surface of the ceramic layer is observed at a magnification of 50,000 times, and 100μm×100μm is randomly selected on the surface of the ceramic layer, and the number of holes with a diameter ≥0.5μm and the number of first polymer particles are counted respectively.
2. The diaphragm according to claim 1, wherein 2≤D1 / D2≤15; and / or, D1 is 0.5 μm-10 μm; and / or, D2 is 0.1 μm-3 μm; and / or, within an arbitrarily selected range of 100 μm×100 μm on the surface of the ceramic layer, the number of holes with a diameter ≥ 0.5 μm is 50-500; And / or, within an arbitrarily selected range of 100 μm×100 μm on the surface of the ceramic layer, the number of the first polymer particles is 30-300.
3. The diaphragm according to claim 2, wherein: D1 is 2μm-8μm; And / or, D2 is 0.5 μm-2 μm.
4. The diaphragm according to any one of claims 1 to 3, wherein: The diaphragm satisfies the following relationship: 1≤D3 / H1≤5, wherein D3 is the average particle size of the first polymer particles in the ceramic layer, in μm; H1 is the thickness of the ceramic layer, in μm; And / or, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 75%-98%, and the weight content of the first polymer is 1%-18%.
5. The diaphragm according to claim 4, wherein D3 is 2μm-10μm; And / or, H1 is 1 μm-5 μm.
6. The diaphragm according to claim 5, wherein D3 is 3μm-6μm; And / or, H1 is 1.5 μm-3 μm.
7. The diaphragm according to any one of claims 1 to 3, wherein: Based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 20%-70%; And / or, the coverage rate of the first polymer particles on the surface of the ceramic layer is 5%-25%.
8. The diaphragm according to claim 7, wherein: Based on the total volume of the pores in the ceramic layer, the volume of pores with a diameter of ≥0.5 μm accounts for 30%-60%; And / or, the coverage rate of the first polymer particles on the surface of the ceramic layer is 8%-20%.
9. The diaphragm according to any one of claims 1 to 3, wherein: The inorganic particles include one or more of aluminum oxide, boehmite, magnesium oxide, magnesium hydroxide, barium sulfate, barium titanate, zinc oxide, calcium oxide, silicon dioxide, silicon carbide, and boron nitride; And / or, the first polymer further includes a third monomer, and the third monomer includes one or more of acrylic acid, butadiene, methacrylic acid, acrylamide, hydroxymethyl acrylamide, hydroxyethyl acrylamide, isopropyl acrylamide, glycidyl (meth)acrylate and allyl glycidyl ester.
10. The diaphragm according to claim 9, wherein The acrylic acid ester monomers include one or more of methyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate.
11. The diaphragm according to claim 9, wherein The styrene monomer includes one or more of styrene, methylstyrene, triphenylethylene and 4-methylstyrene.
12. The diaphragm according to claim 9, wherein: The acrylonitrile monomers include one or more of acrylonitrile, triphenyl acrylonitrile, 3-cyclopentyl acrylonitrile and 3,3-(diphenyl) acrylonitrile.
13. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator located between the positive electrode sheet and the negative electrode sheet, and the separator is the separator according to any one of claims 1 to 12.
14. The battery according to claim 13, wherein The electrolyte includes an organic solvent, which includes a first organic solvent and a second organic solvent, wherein the first organic solvent includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propyl propionate, ethyl propionate and ethyl acetate, and the second organic solvent includes propylene carbonate and / or ethylene carbonate.
15. The battery according to claim 14, wherein The weight ratio of the first organic solvent to the second organic solvent is (0.05-20):
1.
16. The battery according to claim 15, wherein The weight ratio of the first organic solvent to the second organic solvent is (0.1-10):
1.
17. The battery according to claim 13, wherein The electrolyte includes an organic solvent, and the organic solvent includes ethyl methyl carbonate, ethyl acetate and ethylene carbonate.
18. The battery according to claim 17, wherein The weight ratio of ethyl methyl carbonate, ethyl acetate and ethylene carbonate in the organic solvent is (10%-70%): (10%-70%): (15%-40%).
19. The battery according to claim 14, wherein The electrolyte also includes LiFSI.
20. The battery according to claim 19, wherein The electrolyte further includes an additive, and the additive includes one or more of fluoroethylene carbonate, 1,3-propane sultone, vinylene carbonate, lithium difluorophosphate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate.
21. The battery according to claim 20, wherein Based on the total weight of the electrolyte, the weight content of LiFSI is 2%-20%, and the weight content of the additive is 3%-9%.
22. The battery according to any one of claims 14 to 21, wherein At 60° C.-90° C., the first polymer particles are immersed in the organic solvent of the electrolyte for 2 min-10 min, and the solubility of the first polymer particles is ≤50%.
23. The battery according to claim 22, wherein At 60° C.-90° C., the first polymer particles are immersed in the organic solvent of the electrolyte for 2 min-10 min, and the solubility of the first polymer particles is 1%-20%.
Citation Information
Patent Citations
Diaphragm and battery comprising same
CN112018312A
Membrane for an electrochemical device, electrochemical device comprising the membrane, and method of manufacturing an
CN114868301A